Adducin at the Neuromuscular Junction in Amyotrophic Lateral Sclerosis: Hanging on for Dear Life - Krieger, Charles; Wang, Simon Ji Hau; Yoo, Soo Hyun; Harden, Nicholas (Frontiers in Cellular Neuroscience, 2016)
The neurological dysfunction in amyotrophic lateral sclerosis (ALS)/motor neurone disease (MND) is associated with defective nerve-muscle contacts early in the disease suggesting that perturbations of cell adhesion molecules linking the pre- and post-synaptic components of the neuromuscular junction (NMJ) are involved. To search for candidate proteins implicated in this degenerative process, researchers have studied the Drosophila larval NMJ and find that the cytoskeleton-associated protein, adducin, is ideally placed to regulate synaptic contacts. By controlling the levels of synaptic proteins, adducin can de-stabilize synaptic contacts. Interestingly, elevated levels of phosphorylated adducin have been reported in ALS patients and in a mouse model of the disease. Adducin is regulated by phosphorylation through protein kinase C (PKC), some isoforms of which exhibit Ca2+-dependence, raising the possibility that changes in intracellular Ca2+ might alter PKC activation and secondarily influence adducin phosphorylation. Furthermore, adducin has interactions with the alpha subunit of the Na+/K+-ATPase. Thus, the phosphorylation of adducin may secondarily influence synaptic stability at the NMJ and so influence pre- and post-synaptic integrity at the NMJ in ALS.